SECURITY ANALYSIS ON WEBSITES USING THE INFORMATION SYSTEM ASSESSMENT FRAMEWORK (ISSAF) AND OPEN WEB APPLICATION SECURITY VERSION 4 (OWASPv4) USING THE PENETRATION TESTING METHOD - Ditya Putri Anggraeni; Bita Parga Zen; Mega Pranata (The Republic of Indonesia Defense University, 2022)
At this time in the rapid development of technology, there must be advantages and disadvantages of a system or technology that was created. Within the scope of the website, there are also many security holes that irresponsible parties can enter. The state of the website at the Telkom Purwokerto Institute of Technology, both University and Faculty websites, already uses Hypertext Transfers Protocol Secure (HTTPS). This study used the Information System Security Assessment Framework (ISSAF) and Open Web Application Project (OWASP) frameworks with the Penetration Testing method. This study aims to determine vulnerabilities on the website s1if.ittelkom-pwt.ac.id. The result of performing vulnerabilities is several vulnerabilities to the Institut Teknologi Telkom Purwokerto (ITTP) Informatics Study Program website, including not updating jquery on the ITTP website. Ten tests have been carried out, five tests using ISSAF and five tests using OWSP version 4. When performing vulnerabilities in the ISSAF framework, found robots files.txt on the S1 Informatics website which is quite crucial for s1if.ittelkom-pwt.ac.id website which contains an exploitable sitemap.Â